Correlation of Red Cell Distribution Width Value with Force Expiration Volume One Second in Patients with Stable Chronic Obstructive Lung Disease - Martunis, Martunis; Tarigan, Amira Permatasari; Muntasir, Muntasir; Eyanoer, Putri Chairani (Open access Macedonian journal of medical sciences, 2021)
BACKGROUND: Chronic obstructive pulmonary disease (COPD) patients experience an increase in the number of red blood cells and hemoglobin levels due to body compensation in line with the increased secretion of the hormone erythropoietin which stimulates the production of red blood cells. Studies report that red cell distribution width (RDW) increases with the severity of COPD which raises the opinion that RDW can be used as a biomarker in the evaluation of disease severity in patients with COPD. AIM: This study aims to determine the correlation between the value of RDW and forced expiratory volume in one second (FEV1) in patients with stable COPD. METHODS: This study was a case series study conducted from April to August 2019 at the Department of Pulmonology and Respiratory Medicine, USU Medical Faculty. The research subjects were all COPD patients who visited the Lung Clinic RSUP H Adam Malik, Medan, who were selected by consecutive sampling. Data analysis was performed using the Spearman correlation test. RESULTS: A total of 30 people with COPD who met the criteria were included in this study who were dominated by men (93.3%), aged 50–59 years (46.7%), smokers or former smokers (86.7%), with a body mass index of normoweight (50%), and the degree of airflow obstruction is severe (FEV1 < 30% predicts 50%). There was a weak negative correlation between the RDW value and the FEV1 value in the stable COPD patients who were the study subjects, and the correlation was not statistically significant (p > 0.05). CONCLUSION: There is no significant relationship between RDW and FEV1 values in stable COPD patients.